Raman imaging for the analysis of silicone microplastics and nanoplastics released from a kitchen sealant - Fang, Cheng; Luo, Yunlong; Naidu, Ravi (Frontiers in Chemistry, 2023)
Plastic products are used ubiquitously, which can potentially and secretly release microplastics and nanoplastics, such as from the silicone sealant in kitchen. It is important to develop an effective method to monitor these emerging contaminants, as reported herein. By advancing Raman imaging to characterise microplastics and nanoplastics from hundreds of spectra in a scanning spectrum matrix, not from a single spectrum or a single peak, the signal-noise ratio can be significantly increased, from a statistical point of view. The diffraction of the laser spot usually constrains the imaging resolution (such as at ~300 nm), which is also pushed to the limit in this report by shrinking the scanning pixel size down to ~50 nm, in order to capture and image small nanoplastics effectively. To this end, image re-construction is developed to successfully pick up the meaningful Raman signal and to intentionally avoid the noise. The results indicate the silicone sealant in the kitchen can release significant amount of microplastics and nanoplastics. Overall, the advanced Raman imaging can be employed to characterise the microplastics and even nanoplastics smaller than the diffraction limit of laser, via Raman imaging and image re-construction towards deconvolution.